Mineralogia do solo relacionada ao silício no sistema solo-planta - Dalacorte, Luana (2020)
In the soil, the dynamics of silicon (Si) and its various forms are partly influenced by the dissolution of silicate minerals and by Si exported by plants. However, the effect of crops on soil Si loss and soil mineral alterations are not established well. Thus, this study evaluated whether different current and historic uses of soil can modify the soil mineralogy, in which Si export may be the major mechanism altering soil mineral contents. Two studies were conducted with the following objectives: (1) to evaluate the total and available Si contents in two soil types (Ferralsol and Regosol) under two vegetation types (native forest and grassland) and to estimate the potential changes in soil mineralogy associated with the Si forms; (2) to evaluate the total and available Si contents and the changes in Ferralsol mineralogy under different historic soil uses (grassland and soybean cropping over 2, 8, and 40 years). Additionally, the Si contents in plants (roots and shoots) were determined, and a semi-quantification of the phytoliths both in the grassland and in the field under 40 years of soybean planting was performed. The results demonstrated that the levels of available Si in the soil were different according to the soil use and soil type. The lowest values of available and total Si contents were found in the Ferralsol under grassland. Long-term cropping (40 years) did not influence the available Si content but reduced the total Si content in the soil’s clay fraction. Mineral changes were evidenced in the fine soil fraction cultivated for 40 years, where illite was absent, cristobalite and kaolinite were decreased, and the relative amount of quartz was increased. The total Si content in the root and aerial parts of the plants of the grassland site was higher than that of the plants at the crop site. Additionally, at the grassland site, the amount and diversity of phytoliths were higher compared to those at the crop site. It can be concluded that the different current and historic uses of land have modified the soil’s mineralogy. Silicon export by plants is the major mechanism altering the mineral contents in clay. In addition, phytolith formation and recovery in soil are important for maintaining Si cycling in the soil.